Exploring trust dynamics in health information systems: the impact of patients’ health conditions on information source preferences - Song, Mingming; Elson, Joel; Nguyen, Tin; Obasi, Sharon; Pintar, John; Bastola, Dhundy (Frontiers in Public Health, 2024)
IntroductionHealth information systems (HISs) should provide accessible and high-quality information to patients. However, the challenge lies in understanding patients’ trust preferences for health information. This study explores how different information sources (e.g., online platforms, interpersonal sources) are trusted under varying health conditions, focusing on symptom intensity and disease type.MethodsUsing a 2 × 2 × 4 between-subject design, 243 participants from a US college were presented with vignettes of acute or chronic diseases with varying symptom intensities and information sources. Participants rated their trust levels, including both cognitive and behavioral trust, in the health information and recommendations provided by one of the information sources, which was randomly assigned. Logistic regression and ANOVA were employed for the statistical analysis.ResultsThe analysis results revealed that trust is generally higher for interpersonal sources like doctors and family/friends compared to online sources like WebMD and Wikipedia when patients are making health decisions. Doctors are the most trusted source during health-related decision making. However, there are no significant differences in cognitive trust among interpersonal sources or among online sources. Furthermore, symptom intensity and disease type did not significantly alter trust levels across various information sources. These findings suggest that people prefer professional medical advice regardless of their health conditions.DiscussionThe study highlights the need for HIS to incorporate features that provide “doctor-verified” information and promote interactive engagement to enhance patients’ trust in information source. Additionally, it distinguishes between cognitive and behavioral trust, revealing distinct trust patterns that can inform the strategic development of HIS for varied health conditions. Understanding these trust dynamics can inform the design of effective, patient-centered HIS that better support health education, information seeking, and decision-making.